2001
DOI: 10.1309/0bl4-6h9v-dqvv-ugxr
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Factors That Influence the ASCUS/SIL Ratio of Pathologists

Abstract: In pursuit of physician-specific performance data in cytology, we have been calculating the ASCUS/SIL (atypical squamous cells of undetermined significance/squamous intraepithelial lesion) ratio of cytopathologists (CPs) and providing confidential feedback every 6 months. At the same time, thin-layer technology was introduced as an alternative to conventional smears. Thus we analyzed factors that may influence the ASCUS/SIL ratio, particularly the effect of periodic feedback on outliers (defined by a professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 5 publications
2
30
0
11
Order By: Relevance
“…Thus, while performance measures such as the required 10% rescreen of negative cases [13,14], the tracking of CT and cytopathologist diagnostic discrepancies [5,6] as well as the atypical squamous cells-to-squamous intraepithelial lesion (ASC/SIL) are all routine in the quanitification of CT quality [15,16,17], the extension of these tools to thyroid FNA is less straightforward [18,19]. This is because the parallels between indeterminate diagnoses in gynecological cytopathology and thyroid cytopathology are few and tenuous.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while performance measures such as the required 10% rescreen of negative cases [13,14], the tracking of CT and cytopathologist diagnostic discrepancies [5,6] as well as the atypical squamous cells-to-squamous intraepithelial lesion (ASC/SIL) are all routine in the quanitification of CT quality [15,16,17], the extension of these tools to thyroid FNA is less straightforward [18,19]. This is because the parallels between indeterminate diagnoses in gynecological cytopathology and thyroid cytopathology are few and tenuous.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cytopathologists in our laboratory receive annual confidential feedback on certain metrics, including turnaround time, and, for gynecologic specimens, their ASCUS-to-SIL ratio and HPV positivity rate for ASCUS cases [18,19]. Over the 5-year period studied here, the AUS utilization rate was not routinely measured or reported to cytopathologists, and TBSRTC was formally published only at the conclusion of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][8][9][10]19 Furthermore, because ASCUS and LSIL are the major contributors to ASC and SIL, respectively, the difficulty in differentiating between ASCUS and LSIL is a likely explanation for the wide variation of ASC to SIL ratios between laboratories 1,3 and between cytotechnologists and pathologists, even when they practice at the same institution. [20][21][22][23][24][25][26][27] Previous studies have suggested that the variability among pathologists in the classification of squamous abnormalities may be related to differences in both diagnostic thresholds as well as in diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%